Análise da efetividade das ações de controle da dengue no município de Uberlândia, MG a partir da Matriz FPEEEA - Arantes, Karen Magalhães (2017)
Brazil is the first in the world ranking in occurrence of dengue. Dengue is a challenge for public health, its control is complex and is related to social, cultural, environmental, economic and political conditions, due to the several factors that are important determinants in the maintenance and dispersion of both the disease and its transmitting vector. The present study aimed to select and analyze indicators conditioning the dengue proliferation, organizing them according to the FPEEEA framework from WHO for the city of Uberlândia-MG, in addition to evaluating the effectiveness of the actions taken to control dengue in this municipality. A descriptive and exploratory study was carried out with a qualitative and quantitative approach to the analysis of secondary data available in virtual public domain databases related to the social, economic and environmental conditions of Uberlândia-MG, including records of dengue cases reported, as well as information regarding vector control actions. Correlations between selected indicators were performed. From the survey and organization of the information obtained, it was possible to select and propose indicators and information for each axis of the FPEEEA framework, as well as to relate attention and vigilance actions for dengue control. In addition, important correlations were observed between the indicators that make up the different axes of the FPEEEA framework, as well as the absence of correlation between indicators that are considered by the scientific literature as important factors for the occurrence of dengue. Thus, it was observed that many causes contribute to increase the incidence of dengue in Uberlândia and that there are several actions that can be effective for the control of the disease, such as the implementation of policies based on intersectoriality, in order to involve and hold managers and society accountable. The FPEEEA / WHO framework has been shown to be an important tool for the elaboration and planning of surveillance actions involving disease and vector control.